PERENCANAAN LANSKAP JALAN IR. H. JUANDA, KOTA DEPOK - Inke Resunda; Nizar Nasrullah (http://arl.faperta.ipb.ac.id/, 2010)
Depok as developing city has mayor attention in transportation sector. One of the problems was the insufficient alternative way within city, and that has caused traffic jam. One solution offered is developing Ir. H. Juanda Street as primary collector road that links the east to the west side of the city. Within 4 km length and 21,8 m right of way (ROW), the street is passed by Ciliwung river, and it is planned to be a functional and aesthetic streetscape. The aim of this study were to plan a streetscape which is ableto accommodate users needs safely an, comfortably; and also to improve environment quality and to create identity. The spatial plan consisted of circulationarea (32,6%), buffer area (36,4%), service area (22,8%), and identity area (8,2%). Circulation area is for vehicle; buffer area is as buffer and conservation;service as area for users activities; while identity is designate as aesthetic welcoming area. Facilities to be served on site among others are trash basket, pedestrian walk, public phone, sitting area, etc.